Fixed Income Attribution. - Colin, Andrew (John Wiley & Sons, 2005)
Fixed income attribution is by its very nature a complex and mathematically demanding topic, and there is little information available on this area. Fixed Income Attribution has been written to fill this tremendous void. This comprehensive resource contains both theoretical and practical information about running and understanding fixed income attribution, including the mathematics of attribution, practical limitations, benchmarks, presentation tools, and choosing and running an attribution system.